2020
DOI: 10.20944/preprints202002.0248.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predictive Modeling of Henry’s Law Constant in Chemical Structures Using LSSVM and ANFIS Algorithms

Abstract: Henry's constants for different existing compounds in water have great importance in transfer calculations. Measurement of these constants face different difficulties including high costs of experiment and low accuracy of measurement apparatus. Due to these facts, proposing a low cost and accurate approach becomes highlighted. To this end, adaptive neuro-fuzzy inference system (ANFIS) and least squares support vector machine (LSSVM) have been used as Henry's constant predictor tools. The molecular structure of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
0
0
Order By: Relevance
“…The authors reported the mean squared error (MSE) and RMSE for the ANFIS model as 0.0072 and 0.0097, respectively. However, they did not provide details about the structural effect on HLC prediction [18].…”
Section: Introductionmentioning
confidence: 99%
“…The authors reported the mean squared error (MSE) and RMSE for the ANFIS model as 0.0072 and 0.0097, respectively. However, they did not provide details about the structural effect on HLC prediction [18].…”
Section: Introductionmentioning
confidence: 99%